Pengembangan Media Flipbook Dalam Pembelajaran IPS Pada Siswa Kelas III SD - Widiya Widiya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research is motivated by developments in the times that are increasingly leading to technology. Therefore, research that uses technology as a learning medium, namely flipbooks as a piece of software that can facilitate the learning process for third-grade elementary school students on the material